Combined Percutaneous Tracheostomy and Endoscopic Gastrostomy Tubes in COVID-19: A Prospective Series of Patient Outcomes. (October 2021) - Oberg, Catherine L.; Keyes, Colleen; Panchabhai, Tanmay S.; Sajawal Ali, Muhammed; Oh, Scott S.; Grogan, Tristan R.; Mojica, James; Auchincloss, Hugh; Pulido, Natalie; Brait, Kelsey; Folch, Erik E.
Background: A significant number of patients with severe respiratory failure related to COVID-19 require prolonged mechanical ventilation. Minimal data exists regarding the timing, safety, and efficacy of combined bedside percutaneous tracheostomy and endoscopy gastrostomy tube placement in these patients. The safety for healthcare providers is also in question. This study's objective was to evaluate the effectiveness and safety of combined bedside tracheostomy and gastrostomy tube placement in COVID-19 patients.Design and Methods: This is a single arm, prospective cohort study in patients with COVID-19 and acute respiratory failure requiring prolonged mechanical ventilation who underwent bedside tracheostomy and percutaneous endoscopic gastrostomy placement. Detailed clinical and procedural data were collected. Descriptive statistics were employed and time to event curves were estimated and plotted using the Kaplan Meier method for clinically relevant prespecified endpoints.Results: Among 58 patients, the median total intensive care unit (ICU) length of stay was 29 days (24.7-33.3) with a median of 10 days (6.3-13.7) postprocedure. Nearly 88% of patients were weaned from mechanical ventilation postprocedure at a median of 9 days (6-12); 94% of these were decannulated. Sixty-day mortality was 10.3%. Almost 90% of patients were discharged alive from the hospital. All procedures were done at bedside with no patient transfer required out of the ICU. A median of 3.0 healthcare personnel total were present in the room per procedure.Conclusion: This study shows that survival of critically ill COVID-19 patients after tracheostomy and gastrostomy was nearly 90%. The time-to-event curves are encouraging regarding time to weaning, downsizing, decannulation, and discharge. A combined procedure minimizes the risk of virus transmission to healthcare providers in addition to decreasing the number of anesthetic episodes, transfusions, and transfers patients must undergo. This approach should be considered in critically ill COVID-19 patients requiring prolonged mechanical ventilation.